Differences of Fixed Lift Net Catch Result by Using CFL Lamps and Underwater LED in Banten Bay Water - M Johar Rudin; Ririn Irnawati; Ani Rahmawati (Jurnal Perikanan dan Kelautan, 2017)
The utilization of lamps as fishing aids related with the behavior of fish who like light. The lamp who use in this research are Compact Fluorescent Lamp (CFL) and Light Emitting Diode (LED). The purposes is know the illumination of light on the water medium and the composition of the catch of the tap on the CFL and underwater LED. The research was conducted from March to June 2017, located in the Banten Bay Water which has direction of position 05057'873" LS and 106009'486" BT and 06000'158" LS and 106012'011" BT. The experimental method fishing was used in this research. Measurements are made by comparing the illumination of the lamp light 65 watt CFL totaling 8 pieces and combined lamps (1 underwater LED and 6 CFL lamps) on the water medium of fixed lift net. The light illumination was analyzed with  XY graph (Scatter) Microsoft excel 2007 and counter map Surfer v.11. The type and number of fish catch were reported as the data and the composition of the catch was analyzed by comparative descriptive. The average illumination of light on water medium produced 8 CFL and combined lamps respectively of 18.93% and 20.54% that include into the water. Composition of the catch using fishing tools with CFL lamps and a combination of positive phototaxis fish were 172.01 kg (17.42%) and 225.20 kg (22.80%) while the negative phototaxis were 205.59 kg (20.82%) and 384.60 kg (38.95%).